Chinese Children’s Reading Acquisition
XIII, 266 p.
Keywords: Published research and conference presentations on the Chinese language in the last decade have tended to focus on adult language processing. This book provides a comprehensive resource for the critical discussion of major issues in learning to read Chinese from a child acquisition perspective. The combined contributions from researchers in Asian studies, linguistics, psycholinguistics, psychology, cognitive psychology, reading, and education inform international comparative studies of literacy by making apparent the features of the Chinese culture, language, writing system, and pedagogy that may facilitate or impede the acquisition of literacy.